Estimación del impacto del comercio exterior en el empleo manufacturero en Colombia, 1991 - 2010 (2013)
For the period 1991 to 2010, we measure the international trade impact over the manufacturing employment in Colombia, considering the different effects for each of the main trade partners. To do so, a labour demand equation was estimated using the System Generalized Method of Moments, as well as the available information from the Annual Survey of Manufacturing, the administrative records of exports and imports from DIAN, and the National Accounts from DANE. Econometric estimations produced, for this period, evidence inertia in the Colombian labour market. In addition, a substitution relationship between capital and labour was also found. In particular, imports showed none or a negative effect over employment. Analyses by destiny and origin of trade showed that exports to Venezuela, the Andean Community, Chile, Argentina and U.S.A had a negative or none correlation with employment. Likewise, we found none or a slightly low impact of international trade over the labour skilled and unskilled intensive sectors employment.